Genetic Structuralism Analysis On The Color Out Of Space By H.P. Lovecraft - Bagas Maulana; E. Ngestirosa Endang Woro Kasih; Suprayogi Suprayogi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This study aims to delineate the structural form of the story in H.P. Lovecraft’s Color Out of Space considering from the author biography, the social structure of New England and word view of the author toward the short story. The social structure of short story becomes the genetic or origin of literary work. The analysis of this study applied Lucien Goldman’s genetic structuralism and descriptive qualitative method. The data were gathered from H.P. Lovecraft biography, the social condition of New England society in 1920s, and the view of the author toward the condition of New England society in Color Out of Space. The study found out that Lovecraft view the condition of New England after world war two and the earthquake in New York to delineate the horror, cosmic and color story.